High-Performance Supercapacitor Electrode Obtained by Directly Bonding 2D Materials: Hierarchal MoS2 on Reduced Graphene Oxide - Baig, Mutawara Mahmood; Pervaiz, Erum; Yang, Minghui; Gul, Iftikhar Hussain (Frontiers in Materials, 2020)
Energy storage devices are the ultimate flexible solution to overcome energy deficiency. Need is to find innovative nanomaterials to overcome the lags in efficiency and sustainability. Herein, we report the synthesis of hierarchical MoS2/rGO nanohybrids as electrode material for supercapacitors. Pure phase and flower-shaped molybdenum disulfide (MoS2) nanosheets have been synthesized using a meek hydrothermal method followed by the preparation of MoS2/rGO nanohybrids. The physicochemical aspects have been carefully analyzed along with electrochemical properties using cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) method in the 1 M KCL electrolyte. The capacitance of MoS2 and MoS2/rGO found to be 297 F/g (66 mAh/g or 238 C/g) and 850 F/g (153.5 mAh/g or 552.5 C/g) at 1 A/g respectively, with 95.3% retention in capacitance after 10,000 cycles at 2 A/g. The improved electrochemical performance of the MoS2/rGO electrode could be ascribed to rapid diffusion pathways delivered by rGO and improved redox reactions of hierarchical MoS2 nanosheets owing to the high surface area (391 m2/g). This feature enables a decrease in the entire impedance of electrodes, which agrees with the findings obtained from electrochemical impedance spectroscopy.